Analysis of Moral Disengagement in the Food Security Program for Inmate Rehabilitation - Ayyubi, Shalahuddin Al; Simanjuntak, Meitisa Vanya; Ari Wibowo, Wahyu Dwi (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The rehabilitation of prisoners needs to integrate aspects of skills and moral awareness so that behavioral change can be achieved in a sustainable manner. However, moral disengagement mechanisms such as moral justification, shifting responsibility, and moral evasion often arise and can hinder the effectiveness of rehabilitation programs. The food security independence program at Martapura Class IIB Prison serves as a platform for building discipline, responsibility, and readiness among prisoners to face social reintegration. This study aims to understand the dynamics of moral disengagement among prisoners, identify factors that influence moral awareness, and assess its contribution to the effectiveness of the food security program. A qualitative approach was used through in-depth interviews, participatory observation, and documentation of activity results. The research subjects consisted of three inmates involved in the program from January to April and prison officers as mentors. Data analysis was conducted using source triangulation to obtain a comprehensive picture of interactions and behavioral changes. Research shows that moral disengagement mechanisms can be transformed into positive motivation when prisoners are involved in productive activities. Food security programs foster discipline, active participation, and a sense of responsibility. The dominant factors that increase moral awareness include internal motivation, family support, and collaborative social interaction between prisoners and officers. These findings emphasize the importance of rehabilitation that combines moral, social, and productivity aspects. This approach can increase the effectiveness of rehabilitation programs and better prepare prisoners for social reintegration.Pembinaan narapidana perlu mengintegrasikan aspek keterampilan dan kesadaran moral agar perubahan perilaku dapat tercapai secara berkelanjutan. Namun, mekanisme moral disengagement seperti pembenaran moral, pengalihan tanggung jawab, dan moral evasion sering muncul dan dapat menghambat efektivitas program pembinaan. Program kemandirian ketahanan pangan di Lapas Kelas IIB Martapura menjadi wadah untuk membentuk disiplin, tanggung jawab, serta kesiapan narapidana menghadapi reintegrasi sosial. Penelitian ini bertujuan memahami dinamika moral disengagement narapidana, mengidentifikasi faktor yang memengaruhi kesadaran moral, dan menilai kontribusinya terhadap efektivitas program ketahanan pangan. Pendekatan kualitatif digunakan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi hasil kegiatan. Subjek penelitian terdiri dari tiga narapidana yang terlibat dalam program pada Januari–April serta petugas lapas sebagai pembina. Analisis data dilakukan dengan triangulasi sumber untuk memperoleh gambaran komprehensif mengenai interaksi dan perubahan perilaku. Penelitian menunjukkan bahwa mekanisme moral disengagement dapat dialihkan menjadi motivasi positif ketika narapidana dilibatkan dalam aktivitas produktif. Program ketahanan pangan membentuk kedisiplinan, partisipasi aktif, dan rasa tanggung jawab. Faktor yang dominan meningkatkan kesadaran moral meliputi motivasi internal, dukungan keluarga, dan interaksi sosial kolaboratif antara narapidana dan petugas. Temuan ini menegaskan pentingnya pembinaan yang menggabungkan aspek moral, sosial, dan produktivitas. Pendekatan tersebut dapat meningkatkan efektivitas program pembinaan dan mempersiapkan narapidana secara lebih optimal untuk reintegrasi sosial.